PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA MELALUI EDUKASI VALUE SKILL SKEMA PENCEGAHAN KEKERASAN PEREMPUAN TERHADAP ANAK DI KOTA BANJAR - Mira Andriani; Riza Purnama; Dara Siti Nurjanah; Nova Chalimah Girsang (Journal of Empowerment Community, 2025)
Initiatives for women's empowerment aim to achieve gender equality across various development sectors and to protect women from violence. Child protection efforts aim to uphold children's rights and safeguard them against various forms of violence, exploitation, discrimination, and other forms of mistreatment. Given the rising number of violence victims, concerted efforts from various stakeholders are required to combat this issue. This community service project aims to empower participants to prevent violence against women and children through an educational program covering eight key skill areas: 1. Moral and character education; 2. Market-trend product innovation; 3. Legal education regarding violence against women and children; 4. Business and family financial management; 5. "Instagrammable" product packaging; 6. Product photography education; 7. Emotional management under high-pressure situations; and 8. Parenting teenagers. The project is titled "Empowerment of Female Heads of Households through Value-Skill Education: A Scheme for Preventing Violence Against Women and Children in Banjar City." The program's outcomes include an improved understanding of violence prevention and the establishment of a follow-up plan involving "Say No To Violence" agents of change.